CH3NH3PbI(3-x)(BF4)(x): molecular ion substituted hybrid perovskite - Nagane, Satyawan; Bansode, Umesh P.; Game, Onkar S.; Chhatre, Shraddha; Ogale, Satishchandra (Chemical Communications, 2014)
A molecular ion (BF4-) substituted hybrid perovskite CH3NH3PbI(3-x)(BF4)(x) is synthesized. The substituted perovskite shows significant enhancement in electrical conductivity at low frequencies and improved photoresponse under AM1.5 illumination as compared to the perovskite (CH3NH3PbI3).

Nickel cobalt sulfide nanoneedle array as an effective alternative to pt as a counter electrode in dye sensitized solar cells - Banerjee, Abhik; Upadhyay, Kush Kumar; Bhatnagar, Sumit; Tathavadekar, Mukta; Bansode, Umesh P.; Agarkar, Shruti A.; Ogale, Satishchandra B. (RSC Advances, 2014)
Self supported nickel cobalt sulfide (NCS) nanoneedles are directly formed on FTO glass substrates by sulphurization of nickel cobalt oxide nanoneedles (grown by a hydrothermal method) in the presence of a hydrogen sulfide and argon gas mixture. These NCS nanoneedles when used as a counter electrode for dye sensitized solar cells (DSSCs) show efficient catalytic activity towards the I-/I-3(-) redox couple, and lead to an impressive efficiency of 6.9%, compared with 7.7% obtained with a Pt electrode in similarly constructed devices.

Enhancing efficiency of perovskite solar cell via surface microstructuring: superior grain growth and light harvesting effect - Tathavadekar, Mukta C.; Agarkar, Shruti A.; Game, Onkar S.; Bansode, Umesh P.; Kulkarni, Sneha A.; Mhaisalkar, Subodh G.; Ogale, Satishchandra B. (Solar Energy, 2015)
We have introduced a novel approach to enhance the perovskite solar cell efficiency by controlling the grain growth and light harvesting properties of perovskite crystallites. Instead of using a mesoporous TiO2 layer, we have modified the surface microstructuring of the TiO2 film by dispensing nano assembled TiO2 submicron structures (nanobeads, NBs) on TiO2 compact layer. With this new approach solar cell efficiency was improved significantly through an increase in both J(sc) and V-oc. This high efficiency is attributed to crystallite size of the perovskite phase. These also act as light scattering centers giving higher current density and reduced recombination effects giving higher open circuit voltage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Grain growth; Light harvesting; Perovskite solar cells; TiO2 nanobeads

Hybrid perovskite films by a new variant of pulsed excimer laser deposition: a room-temperature dry process - Bansode, Umesh P.; Naphade, Rounak; Game, Onkar S.; Agarkar, Shruti A.; Ogale, Satishchandra (Journal of Physical Chemistry C, 2015)
A new variant of the classic pulsed laser deposition (PLD) process is introduced as a room-temperature dry process for the growth and stoichiometry control of hybrid perovskite films through the use of nonstoichiometric single target ablation and off-axis growth. Mixed halide hybrid perovskite films nominally represented by CH(3)NH(3)PbI(3-x)A(x) (A = Cl or F) are also grown and are shown to reveal interesting trends in the optical properties and photoresponse. Growth of good quality lead-free CH3NH3SnI3 films is also demonstrated, and the corresponding optical properties are presented. Finally, perovskite solar cells fabricated at room temperature (which makes the process adaptable to flexible substrates) are shown to yield a conversion efficiency of about 7.7%.